Occipital cervical fusion with a vascularized free fibular graft - Myron L Rolle; Rosemary E Henn; David W Low; Phillip B Storm (International Journal of Spine Research - Peertechz Publications, 2019)
Obtaining a solid bony fusion after an extensive skull base and upper cervical spine resection in a patient who has previously received radiation therapy is extremely diffi cult and usually results in pseudoarthrosis. We report a technique that uses a free fi bular graft with an arteriovenous loop for a posterior occipital cervical fusion.